3-Dimensional quantitative analysis of mandibular motion in TMD and healthy subjects: Comparison with clinical observations - Tang, Wen; Wu, Yue; Ma, Jiajun; Svensson, Peter; Wang, Kelun; Zhang, Hengjia; Xie, Lizhe; Yan, Bin (Journal of dentistry, 2025)
To establish a quantitative method for objectively assessing 3-dimensional (3D) mandibular trajectories and comparing clinical evaluations with computational analyses. In total, 184 volunteers were recruited and grouped into control (n = 121) and temporomandibular disorder (TMD) groups (n = 63) according to the dual-axis DC/TMD checklist. 3D trajectories were generated by integrating mandibular motion and cone beam computed tomography (CBCT) records. Via digitalized data processing, the following 3 outcomes were assessed: (1) smoothness using the best-fitting polynomial curve, (2) open-closure separation by measuring the deviation between open-closure phases, and (3) condylar trajectory symmetry by comparing left and right movements. Intraclass Correlation Coefficients (ICC) were used to determine agreement between expert observations and quantitative results. Reference ranges for each parameter from the normal population were calculated. Mann‒Whitney test was used to analyze the features of the trajectories between the two groups. ICC confirmed strong consistency between the parametric variations and expert observations (smoothness: 0.797; open-closure separation: 0.820; left-right symmetry: 0.920). Quantitative analyses revealed significant differences (P < 0.043 for smoothness, P < 0.01 for separation, and P = 0.012 for symmetry) in all comparisons between movement trajectories of normal participants and those with TMD, with the latter group exhibiting greater variation and irregularities. The normal range of smoothness was calculated for condylar trajectories between 0 and 0.25 and 0–0.10 for incisal point trajectories. Open-closure separation normal range was computed between 0 and 2.28 mm for incisal point trajectory, 0–1.90 mm for left condylar trajectory, and 0–1.76 mm for right condylar trajectory. The normal range of symmetry between condylar trajectories was calculated to be between 0 and 4.21 mm. This quantitative analysis was confirmed to be reliable and consistent with expert observations. This allowed for the discovery of substantially quantified differences in smoothness, open-closure separation, and symmetry of the motion trajectories in TMD patients versus controls.